Considering ecological traits of fishes to understand microplastic ingestion across Pacific coastal fisheries - Jasha Dehm; Kelly Thomas Brown; Eseta Drova; Rufino Varea; Joycinette Vosumbe Botleng; Siutiti Fe’ao; Lavata Nivaga; Laura Williams; Brian L. Stockwell; Salanieta Kitolelei; Cherie Morris; Nanise Kuridrani; et al. (PLoS ONE, 2026)
Coastal fisheries are essential to Pacific Island communities, providing vital nutrition, livelihoods, and cultural value, yet microplastic (MP) contamination poses a growing threat to both ecosystem and human health. This study presents a regional assessment of microplastic contamination in coastal fish across four Pacific Island Countries and Territories (Fiji, Tonga, Tuvalu, and Vanuatu), based on the compilation of four methodologically standardized datasets, enabling us to evaluate whether regional patterns of contamination are linked to the ecological traits of fish. A total of 878 fish from 138 species were analysed to reveal widespread ingestion (32.7% prevalence; 0.76 ± 0.05 MPs/individual), with Fiji exhibiting the highest contamination (74.5% frequency). Reef-associated invertivores such as Lethrinus harak showed elevated risks (80% contaminated in Fiji), driven by fiber-dominated particles (65–95%), while ecological traits (benthic feeding, reef habitats) increased exposure compared to nearshore pelagic species. Disparities emerged between nations, with Fiji’s sites exceeding global averages despite remoteness, whereas Vanuatu’s low fish contamination suggests restricted dispersal, successful waste management influences, or differential bioaccumulation pathways. Polypropylene, polyethylene, polyethylene terephthalate, and nylon were the dominant (~11–43%) polymer types across all countries. The findings highlight the essential need to incorporate the Pacific Island data into global pollution assessments to better represent tropical Pacific marine ecosystems. This work establishes a standardized baseline for microplastics in the Pacific coastal fish, providing a framework to guide future research on ecological impacts while highlighting the need to integrate these data into regional and global plastics negotiations. The study underscores the importance of expanding monitoring to underrepresented PICTs to better understand contamination drivers in island ecosystems.